Utilisasi Pelayanan Kesehatan Maternal Oleh Masyarakat Miskin Di Pedesaan Dalam Rangka Kehamilan Aman - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract: Backgrounds and Methods: The objective of this study is to examine the utilization of maternal health services by poor community in the village in order to make pregnancy safer. This study is 'descriptive-explorative', located in by East Java and Nusa Tenggara Timur (NTT) Provinces. The sample are selected purposively